2020
DOI: 10.18291/njwls.122142
|View full text |Cite
|
Sign up to set email alerts
|

Older Women’s Experiences in the Icelandic Workforce – Positive or Negative?

Abstract: The purpose of the study is to gain a deeper understanding of older women’s experiences in the labour market, how they value their job opportunities and perceived attitudes towards them. Qualitative interviews were conducted with seven women aged 57–74 years who all have at least 10 years working experience after they turned 40. Experiencing discrimination in the workforce was often mentioned by the women. Their experience is that men are less discriminated against on grounds of age than women. Older women pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The OECD reported in 2017 that males more often combined work and pensions than females (OECD 2017). From a subjective perspective, one study revealed that women experience that men vs. women are less discriminated on the grounds of age (Sigurðardóttir & Snorradóttir 2020). Gender aspects and being active in working life at older ages should also be reflected through the life course principle of linked lives, which, for example, focuses on people's different assets and obligations in their social contexts, for example, extensive care responsibilities for the family (Elder et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The OECD reported in 2017 that males more often combined work and pensions than females (OECD 2017). From a subjective perspective, one study revealed that women experience that men vs. women are less discriminated on the grounds of age (Sigurðardóttir & Snorradóttir 2020). Gender aspects and being active in working life at older ages should also be reflected through the life course principle of linked lives, which, for example, focuses on people's different assets and obligations in their social contexts, for example, extensive care responsibilities for the family (Elder et al 2003).…”
Section: Discussionmentioning
confidence: 99%